2010
DOI: 10.4111/kju.2010.51.7.463
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combination Perianal-Intrarectal Lidocaine-Prilocaine Cream and Periprostatic Nerve Block for Pain Control during Transrectal Ultrasound Guided Biopsy of the Prostate: A Randomized, Controlled Trial

Abstract: PurposeProstate biopsy for diagnosing cancer can be painful. The efficacy and safety of combination perianal-intrarectal lidocaine-prilocaine (PILP) cream and periprostatic nerve block were compared with nerve block alone during transrectal ultrasound guided prostate biopsy (TRUS-Bx).Materials and MethodsFrom October 2007 to August 2009, 74 men undergoing a transrectal prostate biopsy were randomized into two groups. In group 1, 36 patients received a combination of PILP cream and a periprostatic nerve block; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Autorino et al 18 reviewed that periprostatic nerve blocks required one or more extra needle punctures and can be associated with a higher incidence of infectious complications. Though Noh et al 4 reported in Korean Journal of Urology that the combination of periprostatic nerve block and lidocaine gel instillation showed an excellent performance, it is presumed that trials like this are in their early stage. As the periprostatic nerve block is not yet tried in our hospital either, we compared MAC group with lidocaine jelly group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autorino et al 18 reviewed that periprostatic nerve blocks required one or more extra needle punctures and can be associated with a higher incidence of infectious complications. Though Noh et al 4 reported in Korean Journal of Urology that the combination of periprostatic nerve block and lidocaine gel instillation showed an excellent performance, it is presumed that trials like this are in their early stage. As the periprostatic nerve block is not yet tried in our hospital either, we compared MAC group with lidocaine jelly group.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Some examples of anesthetics that may be used during TRUS-guided biopsies include intrarectal lidocaine gel, periprostatic nerve blockers, sedation and caudal blockage. [4][5][6] Peters et al 7 reported the first use of propofol during TRUS-guided biopsies, and observed significantly decreased patient discomfort. However, they performed sextant biopsies in different with current extended biopsy methods, and cost was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the flowchart of the study inclusion process. There were 18 studies involving 2076 patients finally eligible for the quantitative analysis, including 16 RCTs and two retrospective studies . The risk of bias was presented with a risk of bias graph (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used lidocaine gel 4,10-14 for IRLA, six used lidocaine-prilocaine cream, [15][16][17][18][19][20] three used GTN ointment [21][22][23] and three used a diclofenac suppository. 6,24,25 PPNB was accomplished by a 22-G needle under ultrasound guidance into the neurovascular bundle at the base of the prostate, just lateral to the junction between the prostate and seminal vesicle bilaterally in all, but not specified in three studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…9,10 PPNB effectively reduces the pain due to the insertion of the needle in the prostate but it is ineffective in decreasing the pain of the insertion of the probe into the rectum. 2,8,11 In order to reduce the pain of the probe insertion, drugs should be added that have an effect on the anal sphincter. Diltiazem is a drug that has been used in the treatment of anal fissures.…”
mentioning
confidence: 99%